PENGARUH PEMBELAJARAN THINK TALK WRITE BERBASIS CONTEXTUAL TEACHING AND LEARNING - Khotijah, Siti; Hadisaputro, Subiyanto; M.Si, Soeprodjo (Chemistry in Education, 2013)
The purpose of this research is to determine the influece of Think Talk Write (TTW) learning uses Contextual Teaching and Learning (CTL) on learning product. This research population is X of Senior High School 1 Kaliwungu 2011/2012. The sampling technique which used is cluster random sampling, the result of the draws XE as an experiment class (TTW learning uses CTL) and XD as a control class (conventional learning). The data agregation method in this research is documentation, test, observation, and questionnaire. Final data analysis showed that learning product both classes are normally distributed and have equal variances. In the test of correlation, obtained 0.520 of rb value, which showed a middle correlation. This learning contributes to student learning product is 27%. Classical learning completeness which achieved by experiment and control class are respectively 85.71% and 94.29%. The result of data analysis showed average value of kognitif learning product experiment class 78.6 and control class 70.8. The average value of affective and psychomotor in experimental class is better than the control class. Based on this research, we can conclude that TTW learning uses CTL has a positive influential on learning product in Senior High School 1 Kaliwungu.